Secondary School Students’ Perceptions about STEAM Education in Pakistan: A Gender Perspective - Basharat, Rukshinda; Bugti, Sana Mairaj; Umair, Muhammad (PJDOL, 2025)
STEAM is an acronym of Science, Technology, Engineering, Arts and Mathematics, which focuses on developing the critical thinking and problem solving abilities in students and creates interest towards STEAM subjects. The purpose of this study was to determine the perceptions of secondary school students towards STEAM education in Pakistan. Using random sampling, 338 students were selected for data collection. Questionnaire was used as an instrumental tool for collection of data. IBM SPSS version 22.0 was utilised for analyzing the data. The outcomes of this research study stated that students of both genders in Pakistan have different perceptions about STEAM educational subjects; the tendency of both genders are similar towards the use of technology in education whereas other four subjects show dissimilarity between male and female. Study suggests the students to be active in participation of STEAM education and recommends teachers to keep up to date their students about STEAM by providing them a fair chance to perform STEAM based activities during academic activities so that students can enhance their analytical, cognitive and creative skills. Management should provide a suitable and healthy environment for STEAM education and to ensure the curriculum plan as per STEAM.